Răspuns :
1. x-24+5(a-2b)=69
x-24+35=69
x+11=69
x=58
2. 7(a-2b)-x=9
49-x=9
x=40
3. 2(a-2b)=74-20-x
14=54-x
x=40
x-24+35=69
x+11=69
x=58
2. 7(a-2b)-x=9
49-x=9
x=40
3. 2(a-2b)=74-20-x
14=54-x
x=40
x-24 + 5(a-2b)=69
x-24+ 5*7=69
x-24=69-35
x-24=34
x=34+24
x=58
2) -x +7(a-2b)=9
-x+7*7=9
-x=9-49
-x=-40
x=40
3) x+2a -4b=74-20
x+2 (a-2b)=54
x+ 2*7=54
x=54-14
x=40
x-24+ 5*7=69
x-24=69-35
x-24=34
x=34+24
x=58
2) -x +7(a-2b)=9
-x+7*7=9
-x=9-49
-x=-40
x=40
3) x+2a -4b=74-20
x+2 (a-2b)=54
x+ 2*7=54
x=54-14
x=40